A Novel Design of Robotic hand Based on Bird Claw Model. Issue 1 (August 2021) - Nabi, Fizza Ghulam; Sundaraj, Kenneth; Vijean, Vikneswaran; Shafiq, Muhammad; Planiappan, Rajkumar; Talib, Irsa; Rehman, Hakeem Ur
Abstract: Robots are the best replacement of man power in every field of life because they can work with a better efficiency under hard environments. Recently, plenty of work has been carried out on mimicking the human hand motion. However, most of the designers emphasized on designing new actuating system with less degree of freedom or reduce number of actuators along with enhanced performance. Bird claw motion is a natural example with simpler design and has many advantages over human hand such as less number of joints, easy structure and better grip. In this manuscript we propose a robot model which is based on a pigeon's claw and a hardware structure is implemented to verify that the proposed model contain almost half joints than a human hand and hence offers much lower cost along with easier management. Furthermore, smaller size of the palm also facilitates in handling small items. We have presented software and hardware model of a pigeon's claw in support of the argument.